Idiopathic pulmonary hemosiderosis with cystic lesions: A rare presentation - Godoy, Irma [UNESP] (2000)
This report describes a case of a 49-year-old man with cough, recurrent hemoptysis, and dyspnea during 18 months, presenting with radiological findings of alveolar infiltrate and cystic lesions in left upper lobe. Laboratory studies revealed normocytic hypochromic anemia and normal coagulation tests. C-reactive protein and mucoproteins were negative. Serum protein electrophoresis and complement, urinalysis, serum creatinine, creatinine clearance, and 24-hour urine protein were normal. Tests for antineutrophil cytoplasmic antibodies and anti-glomerular-basement membrane antibodies were negative. Tests for connective tissue diseases were all negative. Histological findings were consistent with those of idiopathic pulmonary hemosiderosis. Radiological finding are discussed.